Digital narratives of the Greek ‘Manosphere’ - Peppa, Matina (Social Cohesion and Development, 2026)
In the era of media convergence, which is characterized by the rise of social media, gender’s representations and constructions are constantly shifting and evolving. The present paper seeks to depict the Greek “manosphere” as a digital social environment that produces and promotes ideas and values related to male identity. Specifically, this study focuses on the digital narratives as well as on the content strategies that prevail over social media and belong to the space of “manosphere.” The ultimate goal is to explore the extent to which these digital narratives reinforce or deconstruct modern/traditional perceptions of masculinity, and if they are contributing (or not) to the polarization of the public on gender issues. The initial findings reveal a Greek subculture that embraces the ideals of masculinity, viewing feminism as an obstacle to national identity, that tends to be associated with traditional Orthodox values. Notably, this culture is not overtly visible but lurks beneath humor and sarcasm.